ANALYSIS OF THE DISCOVERY LEARNING MODEL WITH A SCIENTIFIC APPROACH TO IMPROVE THE LEARNING OUTCOMES OF STUDENTS IN SOCIAL SCIENCES CLASS VI ELEMENTARY SCHOOL - Arif Rahman Hakim Arif; Indra Ulfayani Indra; Meyin Syabira Meyin (Journal of Pedagogical Content Knowledge, 2026)
This study aims to analyze the effectiveness of the Discovery Learning model integrated with a scientific approach in improving student learning outcomes in Social Sciences (IPS) for sixth-grade elementary school students. Discovery Learning emphasizes students’ active involvement in discovering concepts and principles independently through activities such as observation, problem identification, information gathering, data analysis, and conclusion drawing. This learning model provides students with opportunities to construct knowledge through direct learning experiences, thereby strengthening conceptual understanding while developing critical thinking, analytical reasoning, and problem-solving skills. The integration of the scientific approach provides a systematic learning framework through the stages of observing, questioning, collecting information, associating, and communicating. These stages encourage students to actively investigate learning materials, connect information with relevant concepts, and communicate the results of their learning. This study employs a literature review method with a qualitative descriptive approach. Data were obtained from relevant scientific literature, including journal articles, books, research reports, and scholarly publications discussing Discovery Learning, scientific approaches, Social Sciences education, and elementary school learning outcomes. The literature selection process considered the relevance, credibility, and contribution of each source to the research objectives. The collected literature was analyzed through identification, classification, comparison, interpretation, and synthesis of findings. The results of the literature analysis indicate that the integration of Discovery Learning and a scientific approach has considerable potential to improve students’ Social Sciences learning outcomes. The approach promotes active participation, conceptual understanding, critical thinking, problem-solving, and students’ ability to communicate learning results. Therefore, Discovery Learning supported by a scientific approach can serve as an effective alternative for improving the quality of Social Sciences learning at the elementary school level.